Indications and use of, and incidence of major bleeding with, antithrombotic agents in myelodysplastic syndrome. (October 2018) - Sorigue, Marc; Nieto, Javier; Santos-Gomez, Mireia; Sarrate, Edurne; Jiménez, Maria-José; Morales-Indiano, Cristian; Lopez-Viaplana, Laia; Orna, Elisa; Navarro, Jose-Tomas; Ribera, Josep-Maria; Xicoy, Blanca
Highlights: We analyzed use, indication and bleeding with antithrombotic (AT) drugs in MDS. 51/193 (26%) were under antiplatelet and 20/193 (10%) under anticoagulant therapy. Ischemic heart disease and atrial fibrillation were the most common indications. Major bleeding was more common in patients taking AT agents than in controls. The appropriateness of AT therapy needs to be carefully assessed in MDS. Abstract: Myelodysplastic syndrome (MDS) and antithrombotic medication both increase the risk of bleeding. We set out to analyze the prevalence of use, indications and bleeding risk of antithrombotic therapy in patients with MDS in a retrospective, single-center study including all patients with MDS with >20 × 10 9 /L platelets. 193 patients (59% male, median age 75 years) were included; 122 did not receive antithrombotic treatment, 51 received antiplatelet agents and 20 received anticoagulants. The cumulative incidence of major bleeding was higher in both the antiplatelet group (11.8% at 4 years, 95% confidence interval [95%CI]: 4.7–22.3%) and the anticoagulation group (21.2% at 4 years, 95%CI 6–42.5%) than in the control group (2.8% at 4 years 95%CI: 0.7–7.3%). The prevalence of use of antithrombotic medication in this cohort of patients with MDS was high and bleeding risk was increased in these patients.